2019
DOI: 10.3928/19404921-20190612-01
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse-Led Cognitive Training Intervention for Individuals With Type 2 Diabetes

Abstract: Targets: Diabetes increases the risk for cognitive impairment and doubles the rate of cognitive decline after diagnosis. In turn, cognitive dysfunction makes diabetes self-management more difficult. Nurses who help manage these conditions are focused on identifying patients who are at risk of complications, promoting symptom management, and preventing further decline. Therefore, the purpose of this study was to develop and pilot test a nurse-led comprehensive cognitive training intervention for persons with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Cognitive training is a common non-pharmacological intervention to treat people with cognitive impairment (45). An eight-week, nurse-led study of a cognitive training intervention conducted in people with type 2 diabetes found that 58% of participants stated the intervention helped their diabetes self-management, and 74% expressed the desire to continue using the learned cognitive strategies (52). Another online cognitive intervention study found that individuals with diabetes improved scores on selfmanagement, cognition and self-efficacy, with an increased adherence to a proper diet and medications (53).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive training is a common non-pharmacological intervention to treat people with cognitive impairment (45). An eight-week, nurse-led study of a cognitive training intervention conducted in people with type 2 diabetes found that 58% of participants stated the intervention helped their diabetes self-management, and 74% expressed the desire to continue using the learned cognitive strategies (52). Another online cognitive intervention study found that individuals with diabetes improved scores on selfmanagement, cognition and self-efficacy, with an increased adherence to a proper diet and medications (53).…”
Section: Discussionmentioning
confidence: 99%
“…Only a limited number of trials exist that evaluate the impact of cognitive interventions in T2DM [42][43][44][45][46][47], of which only few explore the acceptability of these types of interventions. Our findings are consistent with recent evidence presented by Cuevas et al [91] suggesting individuals with T2DM may be motivated to participate in cognitive activities due to their concerns of developing dementia.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to identify strategies that are not only effective in improving cognition in T2DM, but most importantly, strategies that are feasible and acceptable, allowing for long-term behavioural compliance. Cognitive training interventions (i.e., mental exercises used to target one or more cognitive domains) have previously been identified as a potential strategy for targeting cognitive dysfunction [38][39][40], in which there is now growing evidence for their effective use in T2DM [41][42][43][44][45][46][47], particularly in relation to improving diabetes self-management [45,46]. There is a clear and important need for the development of these types of interventions, especially in the context of frameworks that advocate for strategies that assist in implementing and sustaining the skills, abilities, and knowledge required for optimal diabetes self-care [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…It may also be that increased severity of disease has led to a decrease in leisure activities, exercise, sleep, or functional independence, which have protective effects on cognition [ 59 ]. Additionally, it has been shown that subjective cognitive dysfunction can impact daily self-management of chronic conditions like diabetes [ 10 , 11 ] and quality of life [ 13 , 59 ]. For these reasons, qualitative and quantitative research on subjective cognitive dysfunction in persons at risk for dementia are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of midlife self-reported cognitive dysfunction can be a risk for dementia, sometimes presenting before objective impairments are found with neuropsychological tests [ 9 ]. In addition, self-reported cognitive dysfunction can impact daily self-management of chronic conditions such as diabetes [ 10 , 11 ] as well as quality of life [ 12 , 13 ]. As a result, research on self-reported cognitive dysfunction in persons at risk for mild cognitive impairment has increased [ 14 ].…”
Section: Introductionmentioning
confidence: 99%